Factors affecting adoption of dual-purpose forages in the Philippine uplands - Lapar, Ma. Lucila; Ehui, Simeon K. (Elsevier, 2004)
Various limiting constraints have been shown to affect the widespread adoption of dual-purpose forages as hedgerow species among smallholder farmers in the Philippine uplands. Policy and socio-economic factors affecting adoption of forages have not been investigated with sufficient attention. It is important to examine the role of these factors in addition to the biological aspects affecting adoption. This study identifies the factors affecting adoption of dual-purpose forages by smallholder farmers in the upland areas of the Philippines using an econometric approach. Results indicate that farmers who are more educated, have higher income, and have access to credit are more likely to adopt the dual-purpose forages. Moreover, location also plays a critical role in adoption, suggesting the importance of targeting the promotion of dual-purpose forages to farmers in upland areas with problems of soil erosion and declining grazing areas.